Characterization and Antihyperglycemic Activity of a Polysaccharide from Dioscorea opposita Thunb Roots - Yijun Fan (International Journal of Molecular Sciences, 2015)
A polysaccharide DOTP-80 from Dioscorea opposita Thunb was obtained by using the method of acid water-extraction and ethanol-precipitation. After being purified by chromatography, the structure characteristics of DOTP-80 were established. Based on the calibration curve obtained with standard dextrans, the molecular weight of the polysaccharide fraction DOTP-80 was calculated to be 123 kDa. The results of Infrared spectrum (FT-IR) indicated that the polysaccharide contained the α-configuration of sugar units. GC-MS analysis revealed that DOTP-80 was mainly composed of mannose and glucose. Alloxan-induced diabetic rats and mice models were developed to evaluate the in vivo hypoglycemic activity of the polysaccharide. The results indicated that a high dose DOTP-80 (400 mg/kg) had strong hypoglycemic activity. Moreover, DOTP-80 could increase the level of antioxidant enzymes (SOD) activity in alloxan-induced diabetic mice and stimulate an increase in glucose disposal in diabetic rats. Therefore, the polysaccharide DOTP-80 should be evaluated as a candidate for future studies on diabetes mellitus.